The Effect Of Diabetic Foot Exercises On Lowering Blood Sugar Levels In Type II Patients In RSU Imelda Pekerja Indonesia Medan - Ritonga, Yuni Shanti; Silaban, Nataria Yanti; Septiana, Tri Suci (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Increased prevalence of type 2 Diabetes Mellitus in developed and developing countries so that it becomes a health problem or disease global on society. Therefore type 2 Diabetes Mellitus can be prevented by regular exercise, healthy and regular life. The objectives of this study are to: knowing the effect of foot gymnastics on changes in blood sugar levels in elderly people with type 2 diabetes mellitus at RSU Imelda Pekerja Indonesia Medan. This type of research is experimental with one group pre-post test. The population in this study was 30 elderly people with type 2 Diabetes Mellitus at RSU Imelda Pekerja Indonesia Medan. The samples in this study were all elderly people suffering from type 2 diabetes mellitus at RSU Imelda Pekerja Indonesia as many as 30 elderly. The sampling technique used is total sampling. The data collection method used observation sheets before and after foot gymnastics was given. The statistical test used in this study was Wilcoxon with a α of 0.05. The results of the study found that there were changes in blood sugar levels before and after foot exercise with the mean before foot exercise was 182.80 mg / dl while the mean after foot exercise was 143.13 mg / dl. The results of Wilcoxon's analysis obtained a significance value of p-value = 0.000 < α = 0.05 meaning that there is an influence of foot gymnastics on changes in blood sugar levels of patients with type 2 diabetes mellitus at RSU Imelda Pekerja Indonesia Medan. From the results of foot exercise research can affect the decrease in blood sugar levels, besides that the age of respondents can also affect how often to do physical activity sports such as gymnastics every week.